2022
DOI: 10.1108/ijoes-10-2021-0183
|View full text |Cite
|
Sign up to set email alerts
|

Does stakeholder pressure matter in Islamic banks’ corporate social responsibility and financial performance?

Abstract: Purpose This study aims to examine the impact of stakeholder pressure on Islamic banks’ corporate social responsibility (CSR) practices and financial performance. Design/methodology/approach A close-ended questionnaire was collected from 282 Islamic bank’s branch managers. Partial least square structural equation modeling was used to test the hypothesized model. Both measurement and structural models were found to be fit for this research. Findings Results indicate that all components of stakeholder pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 135 publications
0
7
0
2
Order By: Relevance
“…Therefore, we believe that in line with the fundamental principles of Sharia financing, which aim for mutual benefit and not solely profit, it is only natural that strategic efforts need to be made to increase Sharia financing in Indonesia, both in terms of nominal and market share. Additionally, since several regions in Indonesia have a Muslimmajority population, it is only natural that Islamic banking is a cornerstone of sustainable development, especially in reducing inequality and poverty [5,6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we believe that in line with the fundamental principles of Sharia financing, which aim for mutual benefit and not solely profit, it is only natural that strategic efforts need to be made to increase Sharia financing in Indonesia, both in terms of nominal and market share. Additionally, since several regions in Indonesia have a Muslimmajority population, it is only natural that Islamic banking is a cornerstone of sustainable development, especially in reducing inequality and poverty [5,6].…”
Section: Resultsmentioning
confidence: 99%
“…This potential is deeply rooted in the foundational principles of Islamic finance, such as equity, wealth redistribution, and social welfare, which closely align with the objectives of the SDGs [3,4]. In adherence to these principles, Islamic banking places a significant emphasis on business practices that prioritize not only profitability but also social responsibility and mutual benefit, ultimately leading to en hanced social welfare, including the reduction of unemployment and poverty [5,6]. Extensive research has demonstrated a strong connection between financial inclusion and the reduction of income inequality and poverty [7], with Islamic banking playing a role in fostering inclusivity [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Second, PLS-SEM is useful and generates robust results when the study's objective is to predict key constructs in the framework (Chin et al , 2020). Third, PLS-SEM is well suited to behavioral studies where a set of explanatory variables predict a dependent variable (Ali and Raza, 2017; Ting et al , 2019; Ali et al , 2023; Ali et al , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the previous studies by Haniffa and Hudaib [84] and Platonova, et al [80], this study identifies dimensions and sub-dimensions for CSR disclosure in Islamic banks. Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) and previous research on CSR disclosure [85][86][87][88][89] serve as the basis for developing CSR disclosure categories and items from the Shari'ah perspective. As a result, six key areas of CSR disclosure for the Islamic banks have been established, which are "mission and vision statement", "products and services", "zakat, charity, and benevolent fund", "commitment towards employees", "commitment towards debtors", and "commitment towards the community".…”
Section: Corporate Social Responsibility Disclosure Indexmentioning
confidence: 99%